CROCIN EFFECTS ON THE NICOTINE-INDUCED OVARY INJURIES IN FEMALE RAT: Pharmaceutical Sciences-Medicine - ROSHANKHAH, SH.; SALAHSHOOR, M.R.; JALILI, F.; KARIMI, F.; SOHRABI, M; JALILI, C. (International Journal of Life Science and Pharma Research, 2022)
Nicotine is an alkaloid found in tobacco plants. Nicotine decreased estrogen, reduced uterine weight and reduced thickness of the uterus. The Saffron has a special position at people’s eating pattern. Suggesting that saffron may be useful for the treatment of psychological dependence to opioids in humans. Therefore, due to the effects of nicotine on ovary tissue and regard to Crocin properties the aim of this study is to determine the effects of crocin on nicotine induced damage on the female rat ovaries. In this study, 56 wistar immature female rats weighing 30-27 g were used. The mice were randomly assigned to 8 groups. For each ovary, the total follicle was measured after the injection in each groups. Histological, hormonal measurement were done and nitric oxide measurement was performed.The effective dose of nicotine (1 mg/kg) caused a significant decrease in the ovary weight. The stained tissue sections showed that nicotine causes ovarian follicle atresia and administration of Crocin decreased the percentage of atretic follicles. In the Crocin (25,50, 100mg/kg) groups have a significant increase in estrogen, LH and FSH levels in the rat blood serum. By increasing the dose in crocin groups significantly decrease the levels of nitric oxide in blood serum.It seems that nicotine reduces the gonadotropin releasing hormones in hypophysis by exerting its effects on hypothalamus and decreases the growth and development of secondary follicles by reducing the LH and FSH hormones, as a result. Moreover antioxidant properties of Crocin can partly prevent these dysfunctions